Caprylic acid ameliorates rotenone induced inflammation and oxidative stress in the gut-brain axis in Zebrafish - ALTURFAN, EBRU IŞIK (SPRINGER, 2021)
Background Dysfunction of the gastrointestinal tract (GIT) is one of the most common non-motor symptom of Parkinson's Disease (PD). Pathological processes causing PD were suggested to initiate in the enteric nervous system (ENS) and proceed to the central nervous system (CNS). There are studies showing that low-carbohydrate ketogenic diets can improve motor symptoms of PD. Caprylic acid (C8) is the principal fatty acid component of the medium-chain triglycerides in the ketogenic diets. In this study, we aimed to evaluate the effects of caprylic acid, in neurotoxin exposed zebrafish focusing on the relationship between intestinal and brain oxidative stress and inflammation. Methods Adult zebrafish were exposed to rotenone (5 mu g/L) (R group) and caprylic acid (20 and 60 mg/mL) (L + HDCA and R + HDCA groups) for 30 days. At the end of 30 days locomotor activities were determined. Levels of lipid peroxidation (LPO), nitric oxide, glutathione and superoxide dismutase and glutathione S-transferase activities were determined by spectrophotometric methods and gene expressions of tnf alpha, il1, il6, il21, ifn gamma and bdnf were evaluated by RT-PCR in the brain and intestinal tissues of zebrafish. Results Caprylic acid ameliorated LPO, NO, SOD and the expressions of tnf alpha, il1, il6, il21, ifn gamma and bdnf in brain and intestines. Locomotor activities were only ameliorated in high dose R + HDCA group. Conclusions Caprylic acid ameliorated the neurotoxin-induced oxidative stress and inflammation both in the brain and intestines and enhanced locomotor activity in zebrafish.
Keywords: Parkinson's Disease; Caprylic acid; Zebrafish; Rotenone; MEDIUM-CHAIN TRIGLYCERIDES; NEUROTROPHIC FACTOR; PARKINSONS-DISEASE; EXPRESSION; INTESTINE; PLASMA; MODEL; TOOL; RICH; OIL